Soft systems methodology for the implementation of Advanced Manufacturing Technology (AMT) in the South African manufacturing industry - Oluwasola, Awosusi Oluwatosin (My University, 2019)
This research investigated the links between Soft Systems Methodology (SSM) and Advanced Manufacturing Technology (AMT) in the South African manufacturing industry. The research proposed an investigative framework linking AMT Investment and Strategic Planning, the AMT Adoption Process, Barriers and Resistance to Adoption and Benefits Realisation. The research design consisted of a survey using a research instrument and the services of a panel of experts for the verification of the results. The data were collected using electronic surveys using SPSS. The research population was made up of South African manufacturing organisations selected from recognised authorities such as the Financial Mail Survey of the Top 100 companies in South Africa and others. Using the purposive sampling technique, 182 organisations were selected for the study focusing on individuals involved in the selling of AMTs and individuals involved in AMT implementation and operation, as well as AMT investors and decision makers. Two hypotheses were formulated and tested using the Pearson correlation, Spearman’s Rho correlation and t-tests. The findings indicated that organizations which adopt SSM have a stronger statistically significant correlation to success in adopting AMT than organisations using traditional methods. Despite the limitations that were observed, the significant links that were found were used to discuss the findings and it was concluded that SSM presents some advantages when used for the adoption of AMT. Recommendations were made to account for these limitations and areas of improvement for further research were identified.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters of Science in Engineering